Digitalization in Public Finance: A Bibliometric Analysis - Mihail OLARU; Roxana Maria BĂDÎRCEA; Alexandra Lucia ZAHARIA; Alexandru Mihai FIRU; Bogdan NICOLA (Finanţe: Provocările viitorului)
Using bibliometric analysis based on Web of Science data, this study explores the trends and limitations of research digitisation in public finance. Digitization has transformed public finance by leveraging technologies such as e-government platforms, blockchain, and artificial intelligence to modernise public sector operations, resulting in streamlined revenue collection and expenditure management, increased transparency to combat corruption, and real-time data analytics to improve decision making and resource allocation. The study aims to trace the evolution of research on digitisation in public finance, identify key contributors, journals and collaborative networks, analyse thematic clusters and trends, and highlight research gaps while proposing future directions. The study is based on a bibliometric analysis of 298 academic articles (2005-2024) indexed in the Web of Science database and uses VOSviewer software to visualise keyword co-occurrences and bibliometric patterns.